2022
DOI: 10.1097/ju.0000000000002444
|View full text |Cite
|
Sign up to set email alerts
|

En Bloc Resection for Bladder Tumors: An Updated Systematic Review and Meta-Analysis of Its Differential Effect on Safety, Recurrence and Histopathology

Abstract: Purpose: En bloc resection for bladder tumors has been developed to overcome shortcomings of conventional transurethral resection of bladder tumors with regard to safety, pathological evaluation and oncologic outcomes. However, the potential benefits and utility compared to conventional transurethral resection of bladder tumors have not been conclusively demonstrated. We aimed to update the current evidence with focus on the pathological benefits of en bloc resection for nonmuscle-invasive bladder cancer. Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 46 publications
3
34
1
5
Order By: Relevance
“…A recent meta-analysis involving 29 studies also showed that ERBT had a significantly higher DM presence rate in primary ERBT specimens and a significantly lower tumor residual rate in reresection specimens than traditional TURBT. It is consistent with our study ( 23 ). In addition, our study also found that reresection did not seem to improve the prognosis of high-risk NMIBC patients with initial ERBT.…”
Section: Discussionsupporting
confidence: 94%
“…A recent meta-analysis involving 29 studies also showed that ERBT had a significantly higher DM presence rate in primary ERBT specimens and a significantly lower tumor residual rate in reresection specimens than traditional TURBT. It is consistent with our study ( 23 ). In addition, our study also found that reresection did not seem to improve the prognosis of high-risk NMIBC patients with initial ERBT.…”
Section: Discussionsupporting
confidence: 94%
“…In contrast to ‘piecemeal’ resection by cTURB, ERBT incorporates a more delicate en bloc sculpting and tumor excision [ 43 ]. ERBT appears safe, feasible, and effective with demonstrably higher rates of DM in the pathologic specimen and provides better staging [ 6 ]. Given the excellent quality of the initial resection provided by ERBT and evidence supporting the completeness of tumor resection and reduced residual disease, ERBT might result in less need for reTURB.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been increasing evidence to support the clinical benefit of ERBT. Compared to cTURB, ERBT has a higher DM presence rate, seems safer, and yields superior histopathologic information and performance [ 6 , 7 ]. ERBT is most feasible for patients with bladder tumor size of ≤3 cm.…”
Section: Introductionmentioning
confidence: 99%
“…The pooled data of a meta-analysis comparing two RCTs and four observational studies showed a higher rate of detectable muscolaris mucosae in ERBT compared with TURBT (risk ratio: 2.69, 95% CI 1.81–3.97, z = 4.94 and risk ratio: 2.02, 95% CI 1.09–3.75, z = 2.22 for RCTs and observational studies, respectively) [4 ▪ ]. The clinical significance of T1 substaging is still not accepted broadly [23].…”
Section: Quality Of the Pathological Specimenmentioning
confidence: 97%
“…However, the current bulk of evidence provides a low level of evidence and controversial results regarding the superiority of one technique over the other [4 ▪ ,5 ▪▪ ,10].…”
Section: Introductionmentioning
confidence: 99%